Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy307
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Theories of Developmental Psychopathology

Abstract: Interpersonal theories enjoy a long and multidisciplinary history in the field of developmental psychopathology. A core theme is that disruption in developmentally salient interpersonal processes interferes with youths' inherent need for relatedness, creating risk for multiple types of disorders. We review major theories of interpersonal risk—focusing on the family, the peer group, and broader stressful interpersonal contexts—and describe how each theory accounts for the emergence of particular disorders. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 438 publications
2
62
0
Order By: Relevance
“…We interpret these as transdiagnostic bridge symptoms, or symptoms that might be important unifiers of psychopathology in adolescence. Six of these symptoms were again relevant to interpersonal irritability, a finding that is consistent with interpersonal theories of developmental psychopathology, which posit that diverse psychopathologies arise from conflict between interpersonal difficulties and basic needs for kinship (Rudolph, Lansford, & Rodkin, 2016). Particularly given that our longitudinal analyses demonstrated that symptoms of interpersonal irritability predicted future internalizing symptoms (and vice versa), it is intriguing to speculate whether psychological interventions targeting interpersonal irritability would decrease rates of comorbidity between internalizing and externalizing psychopathology.…”
Section: Discussionsupporting
confidence: 76%
“…We interpret these as transdiagnostic bridge symptoms, or symptoms that might be important unifiers of psychopathology in adolescence. Six of these symptoms were again relevant to interpersonal irritability, a finding that is consistent with interpersonal theories of developmental psychopathology, which posit that diverse psychopathologies arise from conflict between interpersonal difficulties and basic needs for kinship (Rudolph, Lansford, & Rodkin, 2016). Particularly given that our longitudinal analyses demonstrated that symptoms of interpersonal irritability predicted future internalizing symptoms (and vice versa), it is intriguing to speculate whether psychological interventions targeting interpersonal irritability would decrease rates of comorbidity between internalizing and externalizing psychopathology.…”
Section: Discussionsupporting
confidence: 76%
“…The family setting is a strategic target for implementing preventive approaches for adolescent depression and anxiety (also known as internalizing) disorders. As posited by interpersonal theories of developmental psychopathology, internalizing problems both result from and contribute to disruptions in developmentally salient interpersonal processes (starting with early parent-infant attachment), which in turn interfere with young people’s need for relatedness [7]. From an etiological perspective, parents have an important influence on young people’s risk for internalizing problems, in terms of both nature and nurture.…”
Section: Introductionmentioning
confidence: 99%
“…Given our a priori focus on the social pain network, we investigated three neural regions of interest (ROIs) that have been implicated as reactive to social feedback in the form of exclusion, including the dACC, sgACC, and anterior insula (Eisenberger, ; Falk et al., ; Masten et al., , ; Sebastian et al., ; for a review, see Rotge et al., ). Adolescent girls were the focus of study given evidence for their heightened sensitivity to social cues (Guyer et al., ), greater emotional reactivity to social stressors (Rudolph, Flynn, Abaied, Groot, & Thompson, ; Rudolph, Lansford, & Rodkin, ; Shih, Eberhart, Hammen, & Brennan, ), including family disturbances (Davies & Windle, ; Rudolph & Flynn, ), and elevated risk for depressive symptoms (Rudolph, ). We predicted that stressful parent–child relationships would be associated with particularly high levels of subsequent depressive symptoms, whereas supportive parent–child relationships would be associated with particularly low levels of subsequent depressive symptoms in girls who showed heightened neural sensitivity to social cues.…”
Section: Potential Trade‐offs Of Biological Sensitivitymentioning
confidence: 99%